Telecommunication system engineering - Freeman, Roger L (Wiley series in telecommunications and signal processing, 1996)
The field of telecommunications is a rapidly growing one, with the bulk of the industry predicated on the telephone or PSTN (Public Switched Telecommunica-tion Network). The primary goal of Telecommunication System Engineering, Third Edition is to describe the development of the PSTN, the rationale behind its structure, and how dramatically it is evolving.